KINERJA GURU DITINJAU DARI SERVANT LEADERSHIP KEPALA SEKOLAH DAN KOMPETENSI GURU DI SMK PASUNDAN KOTA BANDUNG DAN CIMAHI - Arifin, Yusuf; Rustandi, Yus; Rahayu, Kurniawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to Influence Servant Leadership and Teacher Competence on Teacher Performance. Each leader has a different leadership style but still plays an important role in leadership. A leader who serves is a leader with integrity, able to delegate tasks to his subordinates and is effectively carried out if the leader can make the right decisions in all conditions and situations. Servant leadership practices can also be implemented in educational institutions. Schools as academic institutions that carry out the education and learning process for students are highly determined by the leadership practices carried out by the principal. This study aims to analyze the influence of the principal's servant leadership and teacher competence on teacher performance in Vocational High Schools (SMK) within the Pasundan Secondary Basic Education Foundation (YPDM) in the Bandung-Cimahi area. The research method used is a quantitative method with a survey approach. The research sample consisted of 117 teachers who were randomly selected from 165 teachers in several vocational schools in the region. Data was collected through questionnaires and analyzed using path analysis, data analysts using the SmartPLS 4 application The results of the study were descriptive to the three variables studied in the